HUBUNGAN SELF-EFFICACY DAN WORK ENGAGEMENT PADA MAHASISWA/I ILMU FARMASI - Yulia, Yulia; Rohanah, Rohanah; Qomariyah, Lailatul; Suswanti, Ika; Ma'muroh, Ma'muroh (Edu Masda Journal, 2024)
ABSTRACTWork engagement is positive feeling .Work on student is an idea to determine the level of involvement of student in the field of Pharmacy studies. The measuring tool for this research uses the Utrecht work engagement scale for students (UWES-S) 17 items and self-efficacy 10 items. The sample in this study consisted of 86 students from various levels of study in the Pharmaceutical Science department who were already working and were willing to voluntarily fill out a questionnaire distributed online. This research method is quantitative with a cross-sectional study design. The aim of this research is to determine the relationship between self-efficacy and work engagement as indicated by an increase in the cumulative achievement index of students in the field of Pharmacy. The results of this research show that the self-efficacy of Pharmacy Science students has a positive contribution to work engagement which is characterized by vigor, dedication, and absorption. Then, the research results also show that years of education provide a positive relationship with vigor dan dedication. Self-efficacy positive influence on the work involvement of Pharmacy students, where each individual Pharmacy student who has worked, has the ability to divide the time to complete their tasks and has a negative influence to postpone work. The limitation of this research is that it uses samples from certain types of studies.                                                    ABSTRAKWork engagement adalah perasaan positif seseorang terhadap pekerjaannya. Pekerjaan pada pelajar merupakan pikiran untuk menentukan tingkat keterlibatan mahasiswa/i bidang ilmu Farmasi terhadap studinya. Alat ukur penelitian ini menggunakan Utrecht Work Engagement Scale for Students (UWES-S) item 17 dan Self-Efficacy memiliki 10 item. Sampel dalam penelitian ini terdapat 86 mahasiswa/i berbagai tahun tingkatan studi di jurusan ilmu Farmasi yang sudah bekerja yang memiliki kesediaan yang secara sukarela untuk mengisi kuesioner yang disebarkan secara online. Metode penelitian ini adalah kuantitatif dengan desain studi cross-sectional. Tujuan dari penelitian ini adalah untuk mengetahui hubungan self-efficacy dengan  work engagement yang ditunjukan dengan peningkatan nilai indeks prestasi kumulatif mahasiswa/i bidang ilmu Farmasi. Hasil penelitian ini menunjukkan bahwa self-efficacy mahasiswa/i Ilmu Farmasi memiliki kontribusi positif terhadap work engagement yang ditandai dengan vigor, dedication, dan absorption. Kemudian, hasil penelitian juga menunjukkan bahwa tahun pendidikan memberikan hubungan positif yang ditandai dengan vigor dan dedication. Sehingga, sumber daya pribadi seseorang yang pada penelitian ini adalah self-efficacy terhadap keterlibatan kerja mahasiswa/i ilmu Farmasi memberikan pengaruh positif, dimana setiap individu setiap mahasiswa/i Ilmu Farmasi yang telah bekerja, memiliki kemampuan untuk membagi waktu menyelesaikan tugasnya dan memberikan pengaruh negatif untuk menunda pekerjaannya. Keterbatasan pada penelitian ini adalah menggunakan sampel pada jenis studi tertentu.